Al-Istihzā’ dalam Al-Qur’an: Pendekatan Tafsir Maudhu’i terhadap Fenomena Hate Speech di Era Digital - Nasrah Hasugian; Mainnah, Muth; Sihite, Fauzi Hayati; Tarihoran, Saida; Yani, Yuri Indri (Fakultas Tarbiyah dan Kegurusn Universitas Islam Bandung, 2025)
This study aims to analyze the concept of al-istihza’ in the Qur’an through a thematic exegesis (tafsir maudhu’i) approach and to examine its relevance to the phenomenon of hate speech in the digital era. This research employs a qualitative method with a library research approach, using Qur’anic verses as the primary data source. The findings indicate that al-istihza’ in the Qur’an constitutes a form of destructive communication with both theological and social implications, and it shares conceptual intersections with hate speech in terms of communicative function, the normalization of ridicule, and the resulting social impact. The study concludes that the prohibition of al-istihza’ in the Qur’an holds strong normative relevance as a moral foundation for developing digital communication ethics oriented toward respect for human dignity. The implications of this study are both theoretical and practical. Theoretically, it enriches the discourse of thematic Qur’anic exegesis through a contextual approach to contemporary communication issues. Practically, the findings may serve as an ethical reference for Muslims in fostering courteous and responsible digital communication, as well as a normative basis for responding to the phenomenon of hate speech on social media.